Elastase- and LPS-Exposed Cpa3Cre/+ and ST2-/- Mice Develop Unimpaired Obstructive Pulmonary Disease - Cardenas, Eduardo I.; Alvarado-Vazquez, Perla A.; Mendez-Enriquez, Erika; Danielsson, Erik A.; Hallgren, Jenny (Frontiers in Immunology, 2022)
IL 33 and its receptor ST2, as well as mast cells and their mediators, have been implicated in the development of chronic obstructive pulmonary disease (COPD). However, whether mast cells and the ST2 receptor play a critical role in COPD pathophysiology remains unclear. Here, we performed repeated intranasal administrations of porcine pancreatic elastase and LPS for four weeks to study COPD-like disease in wildtype, ST2-deficient, and Cpa3Cre/+ mice, which lack mast cells and have a partial reduction in basophils. Alveolar enlargement and changes in spirometry-like parameters, e.g. increased dynamic compliance and decreased expiratory capacity, were evident one day after the final LPS challenge and worsened over time. The elastase/LPS model also induced mild COPD-like airway inflammation, which encompassed a transient increase in lung mast cell progenitors, but not in mature mast cells. While ST2-deficient and Cpa3Cre/+ mice developed reduced pulmonary function uninterruptedly, they had a defective inflammatory response. Importantly, both ST2-deficient and Cpa3Cre/+ mice had fewer alveolar macrophages, known effector cells in COPD. Elastase/LPS instillation in vivo also caused increased bronchiole contraction in precision cut lung slices challenged with methacholine ex vivo, which occurred in a mast cell-independent fashion. Taken together, our data suggest that the ST2 receptor and mast cells play a minor role in COPD pathophysiology by sustaining alveolar macrophages.